2017
DOI: 10.1016/j.jsps.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of anticancer activity of 6-pyrazolinylcoumarin derivatives

Abstract: A series of novel 6-pyrazolinylcoumarins has been synthesized via multi-step protocol. The synthetic procedure was based on the acetylation of hydroxycoumarins; Fries rearrangement and Claisen-Schmidt condensation; the target 6-[5-aryl-4,5-dihydropyrazol-3-yl]-5-hydroxy-7-methylcoumarins () were obtained under reactions of hydrazine and 2-aryl-5-methyl-2,3-dihydropyrano[2,3-]chromen-4,8-diones as the last phase of the protocol. Anticancer activity screening in NCI60-cell lines assay allowed identification of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Research has shown that substitution on the coumarin scaffold strongly influences its pharmacological profile. Thus, the structural modification of the coumarin core in the pursuit of biologically active multi‐targeting compounds is a constantly intriguing research item (Garazd, Garazd, & Lesyk, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that substitution on the coumarin scaffold strongly influences its pharmacological profile. Thus, the structural modification of the coumarin core in the pursuit of biologically active multi‐targeting compounds is a constantly intriguing research item (Garazd, Garazd, & Lesyk, ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed the significant anticancer activity of different coumarin derivatives against various cancer cell lines including HepG2 and MCF7 cell lines [10][11][12][13][14][15][16][17][18]. Therefore, Novel pyranocoumarin-4-carboxylate derivative 2 was prepared by fusion of the 5-hydroxycoumarin derivative 1 [19] and dimethyl acetylenedicarboxylate (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The multicomponent reaction of the acetylcoumarin derivative 15 [18], malononitrile, ammonium acetate, and 4-chlorobenzaldehyde in ethanol under reflux condition furnished the target 2-aminocoumarinylnicotinonitrile derivative 16. The reaction mechanism was postulated to proceed through initial formation of the coumarin chalcone followed by the nucleophilic attack of malononitrile on the chalcone double bond.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was found that compounds bearing the 3-methoxy-4 hydroxyphenyl and the 4-hydroxyphenyl substituents at position 5 of the pyrazoline fragment were more active than the other analogues. 84 Another study was carried out on the design and synthesis of coumarin derivatives with improved anticancer activity. Among them, oligomerization (di/tri) of coumarin is one of the effective ways.…”
Section: Benzopyrans and Fused Pyranbased Anticancer Scaffoldsmentioning
confidence: 99%